Decontamination of Mikania glomerata Leaves by Gamma Irradiation: Coumarin Determination by HPLC-DAD, Microbiological Control and Genotoxicological Studies - Gouvêa, Marcos Martins; Ferreira-Machado, Samara Cristina; da Silva, Thalita Martins; Lima, Julien Silva; Lau, Cláudio Sérgio Corrêa; Esper, Luciana Maria Ramires; Mourão, Samanta Cardozo; Macedo, Elizabeth Valverde; Vital, Helio de Carvalho; Andrade, Edson Ramos; Netto, Annibal Duarte Pereira; Marques, Flávia Ferreira de Carvalho; Peregrino, Carlos Augusto de Freitas (Planta Medica, 2018)
Gamma irradiation as a decontaminating physical agent could be an important tool in the production chain of herbal medicines by improving the microbiological quality of raw materials and the safety of final products. This study was undertaken to investigate the genotoxic potential and eventual chemical modifications of a batch of Mikania glomerata raw material decontaminated by different doses of gamma irradiation (2.0, 3.5, and 5.0 kGy), using a cesium-137 source. DNA damage was assessed in vitro by agarose gel electrophoresis in regard to double-chain breaks of plasmid pUC 9.1 DNA and in vivo by micronucleus test in bone marrow cells of Wistar rats. Cytotoxicity in bone marrows was assessed by scoring polychromatic and normochromatic erythrocytes ratio. An HPLC-DAD method was adapted and validated for the enhancement of coumarin selectivity from the other matrix constituents. The microbial load was satisfactorily reduced, leading to sterilization at the highest dose. Genotoxic and cytotoxic effects were not increased in the in vitro and in vivo models. The concentration of coumarin and the chromatographic profiles of the hydroalcoholic plant extracts (ethanol 70% v/v) were not modified after such process. Therefore, this work suggests that gamma irradiation of M. glomerata raw material is suitable and safe for microbiological control purposes at the employed doses.
Keywords: gamma irradiation; Mikania glomerate; Asteraceae; microbiological control; HPLC; coumarin content; genotoxicity